Harbor Porpoise (Phocoena phocoena) Reaction to a 3D Seismic Airgun Survey in the North Sea - Sarnocińska, Joanna; Teilmann, Jonas; Balle, Jeppe Dalgaard; van Beest, Floris M.; Delefosse, Matthieu; Tougaard, Jakob (Frontiers in Marine Science, 2020)
The most common cetacean in the North Sea is the harbor porpoise (Phocoena phocoena). Underwater noise is increasingly recognized as a source of impact on the marine environment and seismic airguns were one of the first man-made high intensity sound source to receive attention with respect to potential impact on marine mammals. In this study, we investigate the effects of a 3D seismic survey on harbor porpoise echolocation activity in the Danish sector of the North Sea. This was achieved by deploying porpoise click detectors (C-PODs) and sound recorders (SM2M and SM3M) both inside and adjacent to the seismic survey area, before, during and after the survey over a total duration of 9 months. Three echolocation parameters were analyzed: number of clicks per minute, minutes with porpoise echolocation click trains and feeding buzz frequency in relation to all minutes with click trains. Decreases in echolocation signals were detected up to 8–12 km from the active airguns, which may indicate temporary displacement of porpoises or a change in porpoise echolocation behavior. However, no general displacement of harbor porpoises away from the seismic survey area could be detected when comparing to reference stations 15 km away from any seismic activity. Our results add to the understanding that underwater noise has the potential to affect temporarily foraging efficiency in porpoises. While the effect of seismic surveys on harbor porpoise behavior was smaller than what has been found for pile-driving, the cumulative effect of anthropogenic impacts could be assessed by evaluation of potential population level consequences.